Improving Sewerage Services and Management for Baghdad Citizens using the Rapid Results Approach - World Bank (Washington, DC, 2014)
The Baghdad Sewerage Directorate is responsible for management of the sewerage main trunks, main sewerage pumping stations, and sewerage treatment plants in Baghdad. Each of the 14 municipalities of Baghdad has geographical limits within which they are responsible for maintaining the water supply and sewerage networks. The Deputy Mayor for technical affairs decided to adopt the leadership for results (L4R) approach to facilitate innovative performance improvements in service delivery, working collaboratively with the World Bank leadership practice and the Bank's sectoral management units in the region related to Middle East and North Africa (MENA) public sector management and governance (MNSPS) and MENA water and agriculture (MNSWA). The L4R program provided rapid results training to the leadership, encouraged the establishment of a team that included representatives of all groups concerned, and provided mentoring for coaches and teams, and support to review progress. The L4R program supported training of coaches to facilitate the diagnostic work; an L4R workshop focused on identifying and prioritizing challenges. The Bank trained and supported coaches and mentored the team in conducting a preliminary field survey to estimate the costs of new technologies and in activating the citizen hotline and complaint mechanism.